A combined thermo-kinetic analysis of various methane reforming technologies: Comparison with dry reforming. (January 2017) - Challiwala, M.S.; Ghouri, M.M.; Linke, P.; El-Halwagi, M.M.; Elbashir, N.O.
Graphical abstract: Highlights: Developed energy integrated combined reformer that tackle Dry Reforming challenges. Measured Combined Reformer performance using thermodynamic and kinetic methods. Optimized the process to eliminate carbon deposition. Accounted for thermodynamic non-idealities using different cubic equations of state. Abstract: Dry reforming of methane is one of the few chemical reactions which can effectively convert carbon dioxide (CO2 ), a major green-house gas, into a valuable chemical precursor, syngas (a mixture of CO and H2 ), that can be converted into chemicals and fuels via different synthesis routes such as the Fischer Tropsch synthesis. The inherent limitations of dry reforming reaction, for instance, rapid catalyst deactivation by coke deposition and the very high energy requirements, has restricted its use as a commercial technology. This study was performed to evaluate the potential of overcoming the limitations of dry reforming by integrating it with other commercial methane reforming technologies such as steam reforming and partial oxidation reforming in the context of industrial operating conditions. A thermodynamic and kinetic analysis of the combined reforming has been conducted using the software suite MATLAB ® . The aim of this complicated assessment is to identify optimized combination of the three reformers and also the corresponding operating conditions that would utilize significant amount of CO2 while ensuring CO2 fixation, minimum carbon formation and optimum energy requirements. The thermodynamic equilibrium product distribution calculations involved the Peng Robinson (PR), Redlich Kwong (RK) and Soave Redlich Kwong (SRK) equations of state (EOS) to identify the best EOS that accounts for the non-ideality associated with the high pressure operation. The study evaluated simultaneous effects of temperature (200 °C–1200 °C), pressure (1–20 bar) and feed mole ratios (of methane, steam, carbon dioxide and oxygen) on the equilibrium product distribution. The addition of oxygen and steam to dry reforming helped in decreasing energy requirements while simultaneously increasing the syngas yield ratio (H2 :CO ratio). The numerical evaluation revealed an optimized operating condition of ∼750 °C at 1 bar pressure at a feed mole ratio CH4 :H2 O:O2 :CO2 of 1:0.4:0.3:1. For this optimization, the system boundaries were limited only to a reformer block without considering the upstream and dowstream processes. At this optimized condition, the carbon deposition was eliminated and the CO2 conversion was observed to be 47.84% with an energy requirement of 180.26 kJ. The study is further extended to include kinetic analysis of combined dry and steam reforming of methane. The preliminary findings of kinetic evaluation indicated an excellent agreement between combined kinetic model with the thermodynamic equilibrium results.